Hubungan Antara Konformitas dengan Perilaku Konsumtif Terhadap Online Shopping Pada Remaja - Diana Ariswanti Triningtyas; Tita Maela Margawati (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2019)
The purpose of this study was to analyze and describe how the relationship between conformity and consumer behavior towards online shopping in adolescents. The research design was carried out using a quantitative-non experimental approach. The study population was adolescents in the scope of the Guidance and Counseling study program at the University of PGRI Madiun. The research sample amounted to 72 students. The sampling technique or sampling technique used in this study is a simple random sampling technique. The technique of data collection is done by a Likert scale. The analysis technique uses simple regression analysis with the help of SPSS Statistical computer programs. The results showed that based on the regression analysis test obtained a significance level of 0.00 (p <0.050; significant), meaning that there was a positive relationship between conformity and consumptive behavior towards online shopping in adolescents. From the results of the study, the suggestions that can be conveyed that consumptive behavior can be avoided by making a shopping plan so that expenditure is not excessive and can control themselves is an important factor in reducing consumptive behavior in adolescents